Changes in body composition and its relations to performance in elite female track and field athletes transitioning to the senior division - Tsukahara, Y.; Torii, S.; Yamasawa, F.; Iwamoto, J.; Otsuka, T.; Goto, H.; Kusakabe, T.; Matsumoto, H.; Akama, T. (Sports, 2020)
Many elite female athletes struggle to maintain performance while transitioning from high school to university-level (senior) sports. This study explores factors of body composition that influenced performance in elite junior female track and field athletes transitioning to the senior division. Forty-two elite female track and field athletes, ranked among the top 100 in Japan, were enrolled in this study. Whole-body mode dual-energy X-ray absorptiometry scans were performed during the post-season of 2016 and 2017. Athletes` performances were assessed using the International Association of Athletics Federation scoring system. Relationships between changes in performance and those in body composition were investigated. There were significant negative correlations between changes in performance and fat mass (FM), and percentage FM (FM%). This was seen in total body and lower extremities, and not in the trunk and upper extremities. In addition, there was a positive correlation between changes in performance and percentage lean mass (LM%). However, there were no correlations between changes in performance and LM and total mass. Elite female track and field athletes transitioning to senior division should decrease their FM and FM% and increase LM%, to sustain or improve performance. It is also more important to monitor changes in body composition than body mass.